2014
DOI: 10.1152/ajpgi.00044.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention in Gastrointestinal Physiology and Disease. Natural products and microbiome

Abstract: The human intestinal tract harbors a complex ecosystem of commensal bacteria that play a fundamental role in the well-being of their host. There is a general consensus that diet rich in plant-based foods has many advantages in relation to the health and well-being of an individual. In adults, diets that have a high proportion of fruit and vegetables and a low consumption of meat are associated with a highly diverse microbiota and are defined by a greater abundance of Prevotella compared with Bacteroides, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 156 publications
(168 reference statements)
1
40
0
Order By: Relevance
“…This dynamic microbiome evolves in a mutualistic relationship with our body (18). Gut microbiota plays many important roles to maintain the host health, including fermentation of indigestible dietary compounds, synthesis of vitamins and other beneficial metabolites, and controlling the balance of our immune system (17, 18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dynamic microbiome evolves in a mutualistic relationship with our body (18). Gut microbiota plays many important roles to maintain the host health, including fermentation of indigestible dietary compounds, synthesis of vitamins and other beneficial metabolites, and controlling the balance of our immune system (17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic microbiome evolves in a mutualistic relationship with our body (18). Gut microbiota plays many important roles to maintain the host health, including fermentation of indigestible dietary compounds, synthesis of vitamins and other beneficial metabolites, and controlling the balance of our immune system (17, 18). Dysbiosis defines a situation in which the composition and/or activities of the gut microbiota are altered due to a deleterious state of our body (19), and has been shown to associate with many diseases, especially obesity (20, 21), diabetes (5, 22), metabolic syndrome (23), cardiovascular disease (24), inflammatory bowel disease (25) and colorectal cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Since several studies have shown that microflora may be altered by diet and that colonic probiotic bacteria can remove mycotoxins via physical binding or inactivation (Bennett & Klich, 2003;Davis & Milner, 2009;Greiner et al, 2014;Haskard, El-Nezami, Kankaanpaa, Salminen, & Aholmas, 2001;Rafter, 2002;Saarela et al, 2000;Saulnier et al, 2009), we determined the effect of honey or quercetin on the endogenous colonic probiotic bacteria, activity of colonic microbial enzyme β-glucuronidase and OTA-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…This microflora is in a dynamic equilibrium that may be altered by diet (Bennett & Klich, 2003;Davis & Milner, 2009;Saarela, Lahteenmaki, Crittenden, Salminen, & Mattila-Sandholm, 2000). Several studies showed that colonic probiotic bacteria can remove mycotoxins via physical binding as a mechanism for mutagen removal (Bennett & Klich, 2003;Davis & Milner, 2009;Greiner, Papineni, & Umar, 2014;Saarela et al, 2000). In addition, the severity of mycotoxin poisoning can be amplified by factors such as vitamin deficiency, caloric deprivation, alcohol abuse and infectious disease status (Greiner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The inability of human modeling to do the same has been a source of frustration for many studies, discouraging researchers from pursuing the field of chemoprevention in human. Moreover, the complexity and the variability of gastrointestinal bacteria and the differences in lifestyle choices can negate the potential therapeutic benefits of many substances [22] . There have been studies proving the ability of alcohol and cigarettes to counteract the effect of polyphenols [23] .…”
mentioning
confidence: 99%